Volatile anesthetics evoke prolonged changes in the proteome of the left ventricule myocardium: defining a molecular basis of cardioprotection? - Kalenka, Armin; Maurer, Martin H.; Feldmann, Robert Enrico; Kuschinsky, Wolfgang; Waschke, Klaus F. (Acta anaesthesiologica Scandinavica, 2006)
Background: Volatile anesthetics can alter cardiac gene and protein expression. Of those underlying molecular changes in gene and protein expression in the myocardium after exposure to volatile anesthetics that have been identified, some of them have been related to cardioprotection. Methods: We used two-dimensional gel electrophoresis and mass spectrometry to identify changes in the protein expression of the left ventricle myocardium of anesthesized rats. We maintained anesthesia for 3 h using isoflurane, sevoflurane or desflurane, respectively, at 1.0 minimum alveolar concentration (MAC) and dissected the left ventricular myocardium either immediately or 72 h after the end of anesthesia. Results: We found changes of at least twofold in 106 proteins of the more than 1.600 protein spots discriminated in each gel. These differentially expressed proteins are associated with functions in glycolysis, mitochondrial respiration and stress response. No obvious difference could be observed between the patterns of differential expression of the three volatile anesthetics. Conclusion: We provide the first study of post-anesthetic protein expression profiles associated with three common volatile anesthetics. These volatile anesthetics promote a distinct change in the myocardial protein expression profile, whereby changes in the expression pattern still exist 72 h after anesthesia. These proteome changes are closely related to cardioprotection and ischemic preconditioning, indicating a common functional signaling of volatile anesthestics.